2016
DOI: 10.1111/jnc.13645
|View full text |Cite
|
Sign up to set email alerts
|

Probing amyloid‐β pathology in transgenic Alzheimer's disease (tgArcSwe) mice using MALDI imaging mass spectrometry

Abstract: The pathological mechanisms underlying Alzheimer's disease (AD) are still not understood. The disease pathology is characterized by the accumulation and aggregation of amyloid-b (Ab) peptides into extracellular plaques, however the factors that promote neurotoxic Ab aggregation remain elusive. Imaging mass spectrometry (IMS) is a powerful technique to comprehensively elucidate the spatial distribution patterns of lipids, peptides and proteins in biological tissues. In the present study, matrix-assisted laser d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
56
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(63 citation statements)
references
References 32 publications
6
56
0
1
Order By: Relevance
“…Here, as previously shown through IHC, Aβ1–40, Aβ1–39, Aβ1–38, and Aβ1–37 were observed along with the commonly recognized Aβ1–42 (Reinert et al ). In agreement with previous observations in tgAPP ArcSwe mice, Aβ1–40 was found in our study to be the primary Aβ peptide species in the observed Aβ plaques (Carlred et al ). No consistent changes of N‐terminally truncated Aβ peptides were detected across all the mice, presumably due to their very low abundance.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Here, as previously shown through IHC, Aβ1–40, Aβ1–39, Aβ1–38, and Aβ1–37 were observed along with the commonly recognized Aβ1–42 (Reinert et al ). In agreement with previous observations in tgAPP ArcSwe mice, Aβ1–40 was found in our study to be the primary Aβ peptide species in the observed Aβ plaques (Carlred et al ). No consistent changes of N‐terminally truncated Aβ peptides were detected across all the mice, presumably due to their very low abundance.…”
Section: Discussionsupporting
confidence: 94%
“…In particular, matrix‐assisted laser desorption/ionization imaging mass spectrometry (MALDI IMS) is a powerful, emerging technology for comprehensively delineating lipid, peptide and protein localizations in situ, while maintaining high chemical specificity (Hanrieder et al ; Hanrieder et al ; Michno et al ). In the context of AD, MALDI IMS has been demonstrated to be a powerful tool to measure Aβ peptide pattern in situ at single plaque resolution (Rohner et al ; Stoeckli et al ; Seeley and Caprioli ; Carlred et al ; Kaya et al ; Kakuda et al ; Michno et al ; Michno et al ; Michno et al ).…”
mentioning
confidence: 99%
“…Particularly, mass spectrometry-based molecular imaging (MSI) has been demonstrated to be a valuable approach in biomedical research. It represents a powerful technology for comprehensive spatial profiling of various chemical species, including inorganics, drugs, metabolites, lipids, neuropeptides and proteins in complex biological matrices151617. In contrast to common molecular and histological imaging techniques, MSI does not require any a priori knowledge of the potential target species.…”
mentioning
confidence: 99%
“…a–f) (Carlred et al . ). In this study, we employed a multivariate image analysis approach to outline pathological features that constitute Aβ plaque pathology and reveal the associated Aβ profiles in individual deposits with different areas of the brain.…”
Section: Maldi Ims Applications To Investigate Cns Disease Pathologymentioning
confidence: 97%
“…Moreover, other plaque‐associated proteins were identified within the same experiment, including microglial derived macrophage inhibitory factor (Carlred et al . ).…”
Section: Maldi Ims Applications To Investigate Cns Disease Pathologymentioning
confidence: 97%